Potential of Type and Benefit Piperaceae for Communities in Tangkahan Forest Area - Dyan Rahmaito Siregar; T. Alief Aththorick; Etti Sartina Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesia has a diversity of plants in highland areas such as hillsides or forests. One example of plant diversity in the highlands or in the hills of the Tangkahan Forest is the various types of Piperaceae. Piperaceae theoretically consists of 13 genera and an estimated number of ± 2,658 species. This study aims to examine and analyze of potential of type and benefit Piperaceae for communities in Tangkahan Forest area. This type of research is descriptive research. This research technique is an observation technique. This research was conducted in March to February 2022. Sampling of Piperaceae was carried out by purposive sampling method by making a line transect of 1600 m long. The data collected in this study in the form of primary data and secondary data. Results of research in the Tangkahan Forest area, 16 species of Piperaceae were found with 2 genera namely Peperomia and Piper, of which 16 species have 3 habitus including herbs, shrubs and lianas spread from an altitude. The study on the utilization of Piperaceae noted that there were 5 species used as ornamental plants, 6 species used as ingredients for medicinal herbs, 2 species used for economic purposes and the other species whose potential use was unknown.